Husain Ibn Manshur Al-Hallaj dan Tasawuf - Abdhillah Shafrianto (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
In the Sufism tradition, to get closer to Allah there are several spiritual paths that can be taken, such as with mahabbah, khauf and so on. In the 9th century H, there was a Sufi who had very controversial views and was even considered heretical by people who were not in line with his thoughts, until at its peak a Sufi was sentenced to death, a Sufi known as al-Hallaj. This study aims to determine the life history of al-Hallaj and the thoughts that are considered controversial. The method used is qualitative and is library research using a historical approach. The results obtained are two things of al-Hallaj's thoughts which are considered very controversial, namely al-hulul and wihdat ash-syuhud, the Hulul that happened to an al-Hallaj is not real and is figurative. In other words, what happens is a spiritual awareness (inner emotion) in a mortal condition.